The relative impact of different 'resistant behavioural responses' on interrogative suggestibility in children: The powerful contribution of 'direct explanation' replies to unanswerable questions. Issue 1 (15th November 2021) - Gudjonsson, Gisli; Vagni, Monia; Maiorano, Tiziana; Giostra, Valeria; Pajardi, Daniela
Abstract: The aim of this study was to investigate the different types of resistant behavioural responses to unanswerable questions, their respective individual contribution to the overall variance in resistance efficacy, and their differential protective effect on repeated questioning, interrogative pressure, and delayed suggestibility. The participants were 360 children aged between 7 and 17 years, 180 of whom were suspected victims of sexual abuse and 180 matched peers for age, sex and IQ. All children completed the Gudjonsson Suggestibility Scale 2. Delayed suggestibility was measured after a 1‐week delay. The findings show that 'don't know', 'direct explanation', and 'no' answers are unrelated response styles that have individual effects on resistance to misleading questions. 'Direct explanation' answers are most stable and robust and increase incrementally with age in children, whilst 'no' answers decline. The findings suggest that 'Don't know', 'direct explanation', and 'no' answers are driven by different cognitive and social processes.